2017
DOI: 10.33145/2304-8336-2017-22-332-338
|View full text |Cite
|
Sign up to set email alerts
|

Radiation induced violations of blood circulation in the ciliary body and changes of the anterior chamber angle in the pathogenesis of glaucoma in clean/up workers of the Chornobyl NPP accident and residents of contaminated areas

Abstract: Мета. Оцінити зміни кровонаповнення ціліарного тіла і стану кута передньої камери ока (КПК) та вивчити їх вплив на патогенез глаукоми у радіаційно опромінених осіб. Матеріали і методи. Використані результати обстеження випадково відібраної групи з 41 учасника ліквідації наслідків аварії на Чорнобильській АЕС (УЛНА на ЧАЕС) і 18 мешканців зони гарантованого добровільного відселення; вік на момент обстеження 45-50 років. Контрольну групу становила 41 особа того ж віку. Стан ку та передньої камери вивчався за доп… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…Our data showed that Chernobyl clean-up workers have a significantly higher risk of involutive changes of the anterior chamber angle (ACA) (trabecular zone sclerosis, pigment deposition and exfoliative particles in it, narrowing of the venous sinus of the sclera, as well as the tendency to ACA constriction in some areas), as compared with the control group (RR = 3.5, 1.27-9.5, χ 2 = 7.48, p = 0.031). According to us, such early onset of ACA morphological changes may lead to an increased incidence of open-angle glaucoma in the long-term period [48]. In a cohort of the liquidators (4017 people) during 13 years of dynamic monitoring (18 years after the Chernobyl accident), glaucoma was diagnosed in 28 patients (6.97 per 1000 persons of the group monitored): the annual incidence was, thus, 0.54 per 1000 persons, with a growth of incidence as the IR dose increases to 0.25 Gy [49].…”
Section: Glaucomamentioning
confidence: 99%
“…Our data showed that Chernobyl clean-up workers have a significantly higher risk of involutive changes of the anterior chamber angle (ACA) (trabecular zone sclerosis, pigment deposition and exfoliative particles in it, narrowing of the venous sinus of the sclera, as well as the tendency to ACA constriction in some areas), as compared with the control group (RR = 3.5, 1.27-9.5, χ 2 = 7.48, p = 0.031). According to us, such early onset of ACA morphological changes may lead to an increased incidence of open-angle glaucoma in the long-term period [48]. In a cohort of the liquidators (4017 people) during 13 years of dynamic monitoring (18 years after the Chernobyl accident), glaucoma was diagnosed in 28 patients (6.97 per 1000 persons of the group monitored): the annual incidence was, thus, 0.54 per 1000 persons, with a growth of incidence as the IR dose increases to 0.25 Gy [49].…”
Section: Glaucomamentioning
confidence: 99%
“…According to the Laws of Ukraine «On the Legal Regime of the Territory Contained by the Chornobyl Accident» and «On the Status and Social Protection of the Affected Citizens» as a result of the Chornobyl disaster « [1,2] that people were subject to medical [3][4][5] and radiological con trol. From 1986 to this time, more than 1.5 million measurements for determining the levels of incor porated radionuclides using whole body counters (WBC) were executed by specialists of the State 94 ЕПІДЕМІОЛОГІЯ ТА ДОЗИМЕТРІЯ ВСТУП Після аварії на Чорнобильській атомній електро станції (ЧАЕС) на територіях, забруднених радіо нуклідами, проживало понад 3 млн осіб, які згідно із Законами України «Про правовий режим терито рії, що зазнала радіоактивного забруднення вна слідок Чорнобильської катастрофи» та «Про статус і соціальний захист громадян, які постраждали внаслідок Чорнобильської катастрофи» [1,2] під лягали медичному [3][4][5] та радіологічному контро лю. З 1986 р. і дотепер фахівцями Державної уста нови «Національний науковий центр радіаційної медицини Національної академії медичних наук України» (ННЦРМ) та регіональними установами, ЕPIDEMIOLOGY AND DOSIMETRY institution «National Research Center for Radiation Medicine of the National Academy of Medical Sciences of Ukraine» (NRCRM) and regional institutions involved in the conduct of indi vidual radiation monitoring of the population on radioactive contaminated territories (RCT).…”
Section: Introductionunclassified